2023
DOI: 10.1200/jco.2023.41.4_suppl.507
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of receiving lenvatinib following immunotherapy in patients with advanced hepatocellular carcinoma.

Abstract: 507 Background: Lenvatinib, a multikinase inhibitor, is an FDA approved treatment for advanced hepatocellular carcinoma (HCC) in the first line setting. Atezolizumab and bevacizumab are considered new standard of care as first line therapy after results of the IMBrave 150 trial. Currently, we do not have data to suggest any second-line treatment after administration of immunotherapy. We describe the clinical outcomes in patients with advanced HCC who received lenvatinib following treatment with immunotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, with the increasing number of drugs available for the treatment of advanced HCC, the correct sequence of treatment (e.g., ICI first vs. TKI first) is currently an active area of research. Several retrospective studies have reported efficacy and safety of lenvatinib in the second-line setting post ICI but prospective data is still lacking [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, with the increasing number of drugs available for the treatment of advanced HCC, the correct sequence of treatment (e.g., ICI first vs. TKI first) is currently an active area of research. Several retrospective studies have reported efficacy and safety of lenvatinib in the second-line setting post ICI but prospective data is still lacking [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have reported efficacy and safety of lenvatinib in the second-line setting post ICI but prospective data is still lacking. 73,74 On a different note, we are now starting to understand that patients with HCC of different etiologies may response to ICI therapies differently, in which some patients may achieve better response with lenvatinib. For example, multiple retrospective analyses have shown that lenvatinib might be more effective than ICI combination in non-viral HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Safety profile was largely consistent with previously studies with the most common grade 3 or higher AEs being hypertension. 31 Hence, lenvatinib showed promising efficacy and tolerable safety as second line therapy after Atezo-Bev. In fact, the latest NCCN, ASCO, ESMO, EASL and KLCA-NCC Korea guidelines also recommend to consider lenvatinib as second-line therapy after Atezo-Bev ( Table 4 ).…”
Section: New or Emerging Rolementioning
confidence: 99%